Effects of 4-Week Tangeretin Supplementation on Cortisol Stress Response Induced by High-Intensity Resistance Exercise: A Randomized Controlled Trial - Liu, Meng; Zhang, Zheng; Qin, Chunli; Lv, Bingqiang; Mo, Shiwei; Lan, Tao; Gao, Binghong (Frontiers in Physiology, 2022)
ABSTRACT Objective: This study aimed to investigate the effects of 4-week tangeretin supplementation on the cortisol stress response induced by high-intensity resistance exercise. Methods: A randomized controlled trial (RCT) of twenty-four soccer players was conducted during the winter training season. The experimental group (EG) took the oral supplement with tangeretin (200 mg/day) and the control group (CG) took placebo for 4 weeks. Before and after the 4-week intervention, all players performed a high intensity bout of resistance exercise to stimulate their cortisol stress responses. Serum cortisol, adreno-corticotropic hormone (ACTH) and superoxide dismutase (SOD) were obtained by collecting blood samples before (PRE), immediately after (P0), and 10 (P10), 20 (P20) and 30 minutes (P30) after the exercise. Results: The serum cortisol level (PRE, P = 0.017; P10, P = 0.010; P20, P = 0.014; P30, P = 0.007) and ACTH (P10, P = 0.037; P30, P = 0.049) of EG significantly decreased after the 4-week intervention. Compared with CG, EG displayed a significantly lower level of the serum cortisol (PRE, P = 0.036; P10, P = 0.031) and ACTH (P30, P = 0.044). Additionally, EG presented significantly higher SOD activity level compared with CG at P30 (P = 0.044). The WBC of EG decreased significantly (PRE, P = 0.037; P30, P = 0.046) and was significantly lower than CG at P20 (P = 0.01) and P30 (P = 0.003). Conclusion: Four-week tangeretin supplementation can reduce serum cortisol and ACTH, which may ameliorate the cortisol stress response in soccer players during high-intensity resistance exercise training. It can also enhance antioxidant capacity, accelerate the elimination of inflammation throughout the body, and shorten recovery time after high-intensity exercise. KEY WORDS: tangeretin, exercise test, cortisol stress responses, resistance exercise, serum cortisol; antioxidant capacity